Nanoformulation of the Broad-Spectrum Hydrophobic Antiviral Vacuolar ATPase Inhibitor Diphyllin in Human Recombinant H-ferritin - Vojnikova, Michaela; Sukupova, Martina; Stefanik, Michal; Strakova, Petra; Haviernik, Jan; Kapolkova, Katerina; Gruberova, Eliska; Raskova, Klara; Michalkova, Hana; Svec, Pavel; Kudlickova, Marie Peskova; Huvarova, Ivana; et al. (International journal of nanomedicine, 2024)
BACKGROUND: As highlighted by recent pandemic outbreaks, antiviral drugs are crucial resources in the global battle against viral diseases. Unfortunately, most antiviral drugs are characterized by a plethora of side effects and low efficiency/poor bioavailability owing to their insolubility. This also applies to the arylnaphthalide lignin family member, diphyllin (Diph). Diph acts as a vacuolar ATPase inhibitor and has been previously identified as a promising candidate with broad-spectrum antiviral activity. However, its physicochemical properties preclude its efficient administration in vivo, complicating preclinical testing. METHODS: We produced human recombinant H- ferritin (HsaFtH) and used it as a delivery vehicle for Diph encapsulation through pH-mediated reversible reassembly of HsaFtH. Diph nanoformulation was subsequently thoroughly characterized and tested for its non-target cytotoxicity and antiviral efficiency using a panel of pathogenic viral strain. RESULTS: We revealed that loading into HsaFtH decreased the undesired cytotoxicity of Diph in mammalian host cells. We also confirmed that encapsulated Diph exhibited slightly lower antiviral activity than free Diph, which may be due to the differential uptake mechanism and kinetics of free Diph and Diph@HsaFtH. Furthermore, we confirmed that the antiviral effect was mediated solely by Diph with no contribution from HsaFtH. CONCLUSION: It was confirmed that HsaFtH is a suitable vehicle that allows easy loading of Diph and production of highly homogeneous nanoparticles dispersion with promising broad-spectrum antiviral activity.
Keywords: Zika virus; TBEV; Nanoparticles; Humans; drug delivery; Hydrophobic and Hydrophilic Interactions; lidé; Recombinant Proteins; WNV; zvířata; vakuolární protonové ATPasy; rekombinantní proteiny; lignany; antivirové látky; nanočástice; Antiviral Agents; Animals; SARS-CoV-2; Vacuolar Proton-Translocating ATPases; Lignans; hydrofobní a hydrofilní interakce